Treatment of Rare Inflammatory Kidney Diseases: Drugs Targeting the Terminal Complement Pathway - Anliker-Ort, Marion; Dingemanse, Jasper; van den Anker, John; Kaufmann, Priska (Frontiers in Immunology, 2020)
The complement system comprises the frontline of the innate immune system. Triggered by pathogenic surface patterns in different pathways, the cascade concludes with the formation of a membrane attack complex (MAC; complement components C5b to C9) and C5a, a potent anaphylatoxin that elicits various inflammatory signals through binding to C5a receptor 1 (C5aR1). Despite its important role in pathogen elimination, priming and recruitment of myeloid cells from the immune system, as well as crosstalk with other physiological systems, inadvertent activation of the complement system can result in self-attack and overreaction in autoinflammatory diseases. Consequently, it constitutes an interesting target for specialized therapies. The paradigm of safe and efficacious terminal complement pathway inhibition has been demonstrated by the approval of eculizumab in paroxysmal nocturnal hematuria. In addition, complement contribution in rare kidney diseases, such as lupus nephritis, IgA nephropathy, atypical hemolytic uremic syndrome, C3 glomerulopathy, or antineutrophil cytoplasmic antibody-associated vasculitis has been demonstrated. This review summarizes the involvement of the terminal effector agents of the complement system in these diseases and provides an overview of inhibitors for complement components C5, C5a, C5aR1, and MAC that are currently in clinical development. Furthermore, a link between increased complement activity and lung damage in severe COVID-19 patients is discussed and the potential for use of complement inhibitors in COVID-19 is presented.